Identification of high-risk factors for prehospital delay for patients with stroke using the risk matrix methods - Gao, Zihan; Liu, Qinqin; Yang, Li; Zhu, Xuemei (Frontiers in Public Health, 2022)
Background: Stroke has become the leading cause of mortality and adult disability in China. The key to treat acute ischemic stroke (AIS) is to open the obstructed blood vessels blocked blood vessels as soon as possible and save ischemic penumbra. However, the thrombolytic rate in China is only 2.5%. Research has been devoted to investigating the causes of prehospital delay, but the exact controllable risk factors for prehospital delay remain uncertain, and a consensus is lacking. We aimed to develop a risk assessment tool to identify the most critical risk factors for prehospital delay for acute ischemic stroke (AIS) patients. Methods: From November 2018 to July 2019, 450 patients with AIS were recruited. Both qualitative and quantitative data were collected. The Delphi technique was used to obtain expert opinions about the importance of the risk indices of two consecutive rounds. Then, we used the risk matrix to identify high-risk factors for prehospital delay for AIS patients. Results: The risk matrix identified the following five critical risk factors that account for prehospital delay after AIS: living in a rural area; no bystanders when stroke occurs; patients and their families lack an understanding of the urgency of stroke treatment; patients and their families do not know that stroke requires thrombolysis or that there is a thrombolysis time window; and the patient self-medicates, does not think that the symptoms are serious, and waits for spontaneous remission. Conclusions: The risk analysis tool used during this study may help prevent prehospital delay for AIS patients.